Evaluation on the Preference of Coffee Shop among the Undergraduate Students with Analytic Hierarchy Process Model - Weng Siew Lam; Mohd Abidin Bakar; Weng Hoe Lam; Jia Wai Chen; Hui Lee Ma (International Journal of Supply Chain Management, 2018)
Emergence of coffee shop in recent years has proven the demand of coffee shop in modern lifestyle. Nowadays, visitation to coffee shop has become a common trend for most of the undergraduate students for group discussion or chatting. This study aims to evaluate the preference of undergraduate students from Universiti Tunku Abdul Rahman in selecting the coffee shop based on multiple criteria. There are 19 respondents participating in this study who have visited all the 4 selected coffee shops which are Simple Coffee, Bean Caf, Starbucks and Old Town White Coffee. An Analytic Hierarchy Process (AHP) model is proposed to determine the weight of criteria, priority of coffee shop selection in terms of each criterion and the overall performance of the coffee shop. The findings show that the most important criterion is cleanliness, followed by flavor, store atmosphere, sales promotion, speed of service, price and location. Starbucks is the most preferred coffee shop while the followings are Simple Coffee, Bean Caf and Old Town White Coffee. The significance of this study is to propose a conceptual framework to identify the most preferred coffee shop and the most important criteria in coffee shop selection among the undergraduate students by using AHP model.